CIF sales terms as a mean to derive additional competitive advantage - Perspective from a trader focusing on commodity requiring MR tanker tonnage - Wong, Joanna Wei Wen (2018)
With growing global profit pools, rising profile of industry leaders and decreasing barriers to entry, commodity trading has thus attracted a large number of new players into the market. The landscape for commodities traders has since changed drastically over the past decades and profit margins were hence eroded because of the increasing competitive intensity and price transparency. As a result, it is necessary for traders to maximize his margins by obtaining the lowest cost and the highest return. Hence, the objective of this project aims to examine whether a trader is able to gain more profits by exploiting the use of incoterms specifically FOB and CIF sales terms through having the control of own tonnage. Due to the statistical nature of this research where it utilizes large amount of data published by Clarkson Research Services (CRS), Baltic Exchange and Bloomberg, a quantitative statistical approach was adopted. Formulas such as the Return on Invested Capital (ROIC) and Coefficient of Variance (CV) was used in the process to determine the risk-adjusted earnings generated across the period of 10 years from 2006 to 2015. Overall, the findings were conclusive in proving the hypotheses and it was found that a trader is able to potentially gain more returns if he is able to control own tonnage as compared to spot-chartering. Hence, he is able to improve his competitive advantage when he purchases on FOB and sell on CIF sales terms with own controlled ship and by the use of these incoterms, it allows him to minimize his freight cost further, thereby generating even greater profits.